Prevalence and factors associated with hearing loss in pediatric beta-thalassemia patients receiving blood transfusion and iron-chelation therapy - Songsermpanyakul, Chaiwat (Journal of Nakornping Hospital, 2024)
Introduction: Thalassemia is one of the most common inherited blood disorders worldwide. Hearing loss is more frequently observed in pediatric thalassemia patients receiving blood transfusions and iron chelation therapy compared to normal children. Studies on risk factors for hearing loss have not yet reached definitive conclusions. Identifying the factors associated with hearing loss in this patient group will help guide the development of appropriate treatment plans for pediatric beta-thalassemia patients undergoing iron chelation therapy in the future. Objectives: To investigate the prevalence and factors associated with hearing loss in pediatric thalassemia patients who receiving blood transfusions and iron-chelation therapy. Methods: This research was a retrospective cross-sectional analytical study conducted on patients receiving treatment at Nakornping hospital. Data were collected from medical records between January 1, 2021 and December 31, 2022. Inclusion criteria included patients diagnosed with beta-thalassemia (ICD10: D56.1) under 15 years of age, receiving iron-chelation therapy, and undergoing annual examinations, including blood ferritin levels and audiometry. Results : Of the 96 patients, 24 experienced hearing loss. Patients with Beta thalassemia/Hemoglobin E exhibited a trend towards increased hearing loss compared to those with Beta thalassemia Major ([AOR 4.57, 95% CI 0.97-21.60, p=0.055). Additionally, deferasirox use was associated with a higher risk of hearing loss compared to deferiprone (AOR 3.38, 95% CI 1.02-11.18, p=0.046). However, receiver operating characteristic (ROC) curve analysis revealed a modest accuracy of 69.21% (95% CI: 59.53-78.90), indicating poor predictive performance. Consequently, despite statistically significant findings, the current predictive model may not be sufficiently robust for clinical implementation. Conclusion: This study suggests potential recommendations for monitoring hearing impairments in children receiving deferasirox, particularly those with Beta thalassemia/Hemoglobin E who require regular blood transfusions. However, the study was limited by its small sample size and lack of longitudinal data. Future studies with larger sample sizes and longitudinal data are necessary to confirm the findings of this study.